On the question of modern industrial reproduction specifics - Rokotyanskaya, Violetta V.; Ganaeva, Esita E.; Usanov, Aleksandr Yu.; Gavel, Olga Yu.; Yu.V, Safronova (Opción, 2020)
One of the most important subjects in today’s researches on reproduction processes is the functional role of industry in economic development. The purpose of this paper is to integrate the functional role of the industrial sector of the economy, which is to ensure the formation of a new reproductive structure. This structure will provide to combine the systemically important patterns of use of limited production resources on priority.